Indirect chiral magnetic exchange through Dzyaloshinskii–Moriya-enhanced RKKY interactions in manganese oxide chains on Ir(100) - Martin Schmitt (Nature Portfolio, 2019)
Manganese oxide self-organizes on Ir(100) surfaces to form arrays of one-dimensional chains, providing a model system to study emergent magnetic behaviour. Schmitt et al. demonstrate they host chiral magnetism mediated by Dzyaloshinskii–Moriya-enhanced RKKY interactions.